Female entrepreneurship and company´s digitalization from the perspective of grounded theory - Tiburcio Sánchez, María Lourdes; Godínez López, Roberto; Salgado Barrera, Jorge Fabrizio; Lozano Montero, Eva (Revista Venezolana de Gerencia, 2026)
Digitalization has radically transformed the economic landscape, democratizing access to markets and resources. However, the gender gap in technology adoption remains as a significant challenge. This study, conducted in Celaya, Guanajuato, aimed to understand the role of women founders in the digitalization of their micro, small, and medium-sized enterprises (MSMEs). The research was framed within a qualitative paradigm and employed a grounded theory design. The reference framework included the Individual Gender Differences Theory (IGDT) and Information Technology (IT) Theory. Twenty interviews (both in-person and online) were conducted between February and June 2025, and the data was analyzed using Atlas.ti v7. The study found that women’s entrepreneurship is driven by profound concerns and fueled by a constant pursuit of training (both empirical and formal). Women utilize technology for management and growth, facing structural and social challenges. Gender stereotypes persist, and the phenomenon of intragender sexism was identified. Formalization and professionalization proved to be key conditions for business sustainability. Women face external, internal, and symbolic barriers that affect their level of digital adoption. Their entrepreneurship is characterized by a dynamic cycle of motivation, learning, and adaptation. This cycle is driven by the aspiration for social impact and collective well-being, beyond the mere pursuit of income.